Long-term nitrogen addition shifts the soil nematode community to bacterivore-dominated and reduces its ecological maturity in a subalpine forest. (March 2019) - Shaw, E. Ashley; Boot, Claudia M.; Moore, John C.; Wall, Diana H.; Baron, Jill S.
Abstract: Nitrogen deposition from anthropogenic sources is a global problem that reaches even the most remote ecosystems. Responses belowground vary by ecosystem, and have feedbacks to geochemical processes, including carbon storage. A long-term nitrogen addition study in a subalpine forest has shown carbon loss over time, atypical for a forest ecosystem. Loss of microbial biomass is likely linked to lower soil carbon, but the mechanism behind this is still unknown. One possible explanation is through increased turnover due to grazing by soil fauna. Because nematodes occupy many trophic levels and are sensitive to trophic and environmental changes, assessing their communities helps reveal belowground responses. In this study, we tested the hypothesis that long-term nitrogen fertilization affects nematode community structure and maturity beneath coniferous forests in the Rocky Mountains, indicating a faster cycling, bacterial-driven system. We identified and enumerated nematodes by trophic group and family from experimental plots. Total nematode abundance was 40–96% greater in fertilized plots compared to the control, but richness, diversity, and ecological maturity were lower. The differences in abundance were driven by opportunistic bacterivores (e.g., Rhabditidae) and plant parasites (e.g., Tylenchidae), which made up 23 and 13% of the community in fertilized compared to 7 and 5% in control plots, respectively. Nematode maturity indices showed that the nematode food web was enriched (indicating high nutrient/resource status) and structured (all trophic levels present, including long-lived predators) in both treatments, but significantly more enriched in the fertilized treatment. Nonmetric multidimensional scaling of the relative abundance of nematode families demonstrated that nematode community composition differed between treatments, driven largely by opportunistic bacterivores (e.g., Rhabditidae) in the fertilized plots. The mechanism of the aboveground–belowground link between nitrogen deposition and nematode community composition is likely through increased microbial turnover, and sustained high-quality food for microbial grazing nematodes. Highlights: Subalpine soil total nematode abundance is higher in fertilized vs. control plots. r -selected bacterivores increase as diversity, maturity decline in fertilized plots. High nutrients could feedback to soil C loss via a microbe-nematode trophic cascade.